A photovoltaic powered wireless charging system for light-duty electric vehicles with reflective panel analysis. Issue 2 (1st June 2023) - Aganti, Mahesh; Chokkalingam, Bharatiraja
ABSTRACT: To reduce the pollution to a large extent in the transportation sector, it is important to charge the Electrical Vehicles (EV) from sustainable sources of electricity, such as solar or wind energy. Building integrated photovoltaic (BIPV) systems have gained popularity over the past 10 years and have been demonstrated to be a practical method of generating renewable energy that can be used to partially power buildings. One of the emerging technologies in EV charging systems is wireless charging technology; we realize that using this technology, fully automatic charging is simple. Compared to a plug-in charging system, wireless charging is free from rust, rain, and other environmental impacts like vandalization and visual pollution. By integrating wireless EV charging with BIPV shading systems, it offers a green and cutting-edge charging option. Building integrated solar panels are affected by different scenarios and causes due to their positioning. The direction of the solar panel, tilted position, and reflected irradiation, these all factors are to be considered in design of BIPV system. In this article, a system designed in way to analyze the effect of white and black color reflectors effect on solar panels (shading system) in different directions. In this work, a 256-W wireless charging system developed for E-bikes utilizing BIPV system. The proposed BIPV-fed resonant inductive charging system achieved efficiency of 95% for simulation and 91.6 for experimental analysis. The experimental analysis is verified by simulation and experimental results.